(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
speech is an important tool for people to communicate. What separates humans from the animal world is speech and thought. In this article, the definitions and similes given to the word in the epic "Khamsa", which is considered Navoi’s famous work, are cited.